Intention to Use GrabFood During the Covid-19 Pandemic - Tan, Woei Uen; Tan, Xue Er; Tan, Yan Chia; Tan, Wei Qi; Almutairi, Reem (AIBPM Publisher, 2022)
With the COVID-19 pandemic today, food delivery is exceptionally well known to individuals. As the pandemic has restricted people from dining in restaurants, the online-based application is an ideal decision. There are many online platforms for food delivery applications such as GrabFood, Foodpanda, and others. These online food delivery applications have become the new norms, and it has brought many benefits to the public. This project highlights the intention of the public to use the GrabFood application in their daily life, as well as to discover their intention to use it. We investigate the depth of GrabFood's application trustworthiness, usefulness, quality, and price. These factors would result in consumer loyalty over the long haul. A survey was conducted by sending the google form to 150 respondents to investigate their intention of using the GrabFood application. The study results showed that GrabFood is acquiring in prevalence during the flare-up of the COVID-19 crisis.Â Keywords: Covid-19, GrabFood, Intention to Use, Trustworthiness, Usefulness.Â